Le nuove disposizioni di vigilanza in materia di controlli interni: le prime evidenze del III pilastro - Rosaria Cerrone (LUISS Guido Carli, Department of Economics and Business, Arcelli Centre for Monetary and Financial Studies, 2013)
– The financial crisis, the position of the standard setters and the new regulation by Bank of Italy about internal controls show new approaches for banks in managing and controlling risks. The regulatory landscape for bans is full of references to risk appetite framework and its benefits. Our goals are to present the effects for Italian banks of the adoption on July 2014 of the new framework; to show the relationship between enterprise risk management and the regulators' interest in appetite framework as a cure for banks' shortcomings in their risk governance. The investors' relations based on Basel 2 Pillar 3 of the five largest Italian banking groups are considered as the existing example of banks' risk management scheme. The results show that Italian banks have reached some results but they must still identify and quantify their risks in a structured way that relates them to firm's business objectives and strategy.
Keywords: G21; G28; 330; enterprise risk management; risk appetite framework; sistemi di controllo interno; attivita' di vigilanza